Mortality of Japanese patients with Leigh syndrome: Effects of age at onset and genetic diagnosis. Issue 4 (10th February 2020) - Ogawa, Erika; Fushimi, Takuya; Ogawa‐Tominaga, Minako; Shimura, Masaru; Tajika, Makiko; Ichimoto, Keiko; Matsunaga, Ayako; Tsuruoka, Tomoko; Ishige, Mika; Fuchigami, Tatsuo; Yamazaki, Taro; Kishita, Yoshihito; et al.
Abstract: Leigh syndrome is a major phenotype of mitochondrial diseases in children. With new therapeutic options being proposed, assessing the mortality and clinical condition of Leigh syndrome patients is crucial for evaluating therapeutics. As data are scarce in Japan, we analysed the mortality rate and clinical condition of Japanese Leigh syndrome patients that we diagnosed since 2007. Data from 166 Japanese patients diagnosed with Leigh syndrome from 2007 to 2017 were reviewed. Patients' present status, method of ventilation and feeding, and degree of disability as of April 2018 was analysed. Overall, 124 (74.7%) were living, 40 (24.1%) were deceased, and 2 (1.2%) were lost to follow‐up. Median age of living patients was 8 years (1‐39 years). Median length of disease course was 91 months for living patients and 23.5 months for deceased patients. Nearly 90% of deaths occurred by age 6. Mortality rate of patients with onset before 6 months of age was significantly higher than that of onset after 6 months. All patients with neonatal onset were either deceased or bedridden. MT‐ATP6 deficiency caused by m.8993T>G mutation and MT‐ND5 deficiency induced a severe form of Leigh syndrome. Patients with NDUFAF6, ECHS1, and SURF1 deficiency had relatively mild symptoms and better survival. The impact of onset age on prognosis varied across the genetic diagnoses. The clinical condition of many patients was poor; however, few did not require mechanical ventilation or tube‐feeding and were not physically dependent. Early disease onset and genetic diagnosis may have prognostic value.